Effect of Pore Geometry on Resistive-Pulse Sensing of DNA Using Track-Etched PET Nanopore Membrane - Kaya, Dila; Dinler, Ali; San, Nevim; Kececi, Kaan (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
We have investigated the effect of nanopore geometry on translocation properties of poly(ethylene terephthalate) (PET) membranes. In order to vary the cone angles of the conically shaped nanopores, which were obtained by track-etch method, we have added different volume fractions of methanol to the alkali etching solution. We have confirmed through the characterization of PET membranes that methanol has a promoting effect on cone angle. Additionally, we have reported the positive influence of a higher cone angle for resistive pulse sensing of 50-bp DNA. We have also shown the change in electric field as a function of cone angle by using finite element simulations and confirmed a higher electric field with increasing cone angle. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Resistive-pulse sensing; track-etched nanopore; stochastic sensing; finite-element simulation; solvent shaping; SOLID-STATE NANOPORES; SINGLE-NANOPARTICLE DETECTION; ATOMIC LAYER DEPOSITION; HEAVY-ION TRACKS; POLYNUCLEOTIDE MOLECULES; ASYMMETRIC NANOPORES; ARTIFICIAL NANOPORE; SYNTHETIC NANOPORES; CONICAL NANOPORES; ALPHA-HEMOLYSIN; Electrochemistry